Pelatihan Pemahaman dan Perhitungan Pajak Bumi dan Bangunan bagi Warga Desa Kubil - Hindayani, Novia; Arum, Mega (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This community service program aims to enhance public understanding and compliance regarding Property Tax (Pajak Bumi dan Bangunan/PBB) in Kp. Kubil, Cipocok Jaya, Serang City. Low awareness in rural areas often leads to miscalculations, late payments, and reduced local revenue. The program was implemented through interactive educational sessions, practical workshops on Property Tax calculation using real-life cases, and consultation sessions to address residents’ specific concerns. The main objective was to equip participants with knowledge about the tax’s role in regional development, proper payment procedures, and how to interpret the Tax Due Notification Letter (SPPT). The results show improved understanding of Property Tax, increased awareness, and greater ability to calculate tax independently. This initiative is expected to improve compliance and local revenue from Property Tax (PBB), ultimately supporting infrastructure development and enhancing public welfare at the village level.